Mitochondrial cytochrome P450 (CYP) 1B1 is responsible for melatonin‐induced apoptosis in neural cancer cells. Issue 1 (25th March 2018) - Yu, Zhenlong; Tian, Xiangge; Peng, Yuling; Sun, Zheng; Wang, Chao; Tang, Ning; Li, Bin; Jian, Yuqing; Wang, Wei; Huo, Xiaokui; Ma, Xiaochi
Abstract: Melatonin is an endogenous indoleamine with a wide range of biological functions in the various organisms from bacteria to mammals. Evidence indicates that melatonin facilitates apoptosis in cancer cells and enhances the antitumor activity of chemotherapy in animals and clinical studies. However, the melatonin metabolism and the key metabolic targets in cancer cells still remain unknown. In this study, U118 and SH‐SY5Y tumor cell lines were used to investigate the metabolic pathways of melatonin in cancer cells. Interestingly, the inhibitory effect of melatonin on proliferation in SH‐SY5Y cells is more potent than that in U118 cells. In contrast, this inhibitory effect on the normal cells is absent. The antitumor effects of melatonin are positively associated with its metabolite N ‐acetylserotonin (NAS). Unexpectedly, CYP1B1 is, for first time, identified to localize in the mitochondria of tumor cells, and it metabolizes melatonin to form NAS in situ, which subsequently triggers mitochondria‐dependent apoptosis in cancer cells. In normal cells, NAS does not induce apoptosis. A remarkable individual variation on CYP1B1 expression was also detected in human tumor tissue. These findings provide the novel mechanisms regarding the antitumor effects of melatonin in the level of mitochondria. Thus, we hypothesize that CYP1B1 overexpression in mitochondria would significantly enhance the antitumor effects of melatonin. Mitochondrial CYP1B1 can potentially serve as a specific target to modify the therapeutic and biological effects of melatonin on cancer patients.